Hubungan Antara Penurunan Laju Filtrasi Glomerulus Dengan Beratnya Anemia Pada Pasien Nefropati Diabetik Di RSUD dr. Sayidiman Magetan - Fadhilah, Ferdy Arif (2016)
Background : Diabetes Mellitus (DM) is one of the most common chronic disease that found in primary health care. A high number of DM cases will increase morbidity and mortality due to its complications. Diabetic Nephropathy (DN) is a complication of diabetes occurs on kidney. In diabetic patients, especially nephropathy, anemia is one of complication caused by the disease. The incidence of anemia increase with higher the DN stage. It happens due to the decreasing of Glomerular Filtration Rate (GFR) especially if < 60 mL/min/1.73 m2. Objective : To know the correlation between the decreasing of GFR and severity of anemia on DN patient in dr. Sayidiman General Hospital of Magetan. Methods : The research is an observational analytic with cross-sectional study approach. Samples is taken by using purposive sampling technique. Total sample are 48 medical records from the patients who suffer DN. Data of research is analyzed by using pearson test. Result : Statistical data analysis obtained r = 0,629 or strong correlation (0,6-0,8) with the correlation positive direction (+) and p < 0,001. Conclusion : There is a correlation between the decreasing of GFR and severity of anemia on DN patient in dr. Sayidiman General Hospital of Magetan.